Respuesta :
2x+y=5 and -5x-2y=-6
Multiply the 1st equation by 2 and you have:
4x+2y=10 now add this to the second equation which cancels out y...you are left with:
-x=4, divide both sides by -1 so that x=-4
Now use either original equation to find y using the value of x that we just found...2x+y=5 becomes:
-8+y=5 add 8 to both sides
y=13
So the solution is (-4,13) and NOT (-4,12)
Multiply the 1st equation by 2 and you have:
4x+2y=10 now add this to the second equation which cancels out y...you are left with:
-x=4, divide both sides by -1 so that x=-4
Now use either original equation to find y using the value of x that we just found...2x+y=5 becomes:
-8+y=5 add 8 to both sides
y=13
So the solution is (-4,13) and NOT (-4,12)
Equation 1) 2x + y = 5
Equation 2) -5x - 2y = -6
Multiply equation 1 by 2, so that both equations have (2y) in it.
1) 2 (2x + y = 5)
1) 4x + 2y = 10
2) -5x - 2y = -6
Add equations together.
x=-4
Plug in (-4) for x in equation 1.
2x + y = 5
2(-4) + y = 5
-8 + y = 5
Add 8 to both sides of the equation.
y = 13
(-4, 13)
So no, (-4, 12) is not the correct answer.
~Hope I helped!~
Equation 2) -5x - 2y = -6
Multiply equation 1 by 2, so that both equations have (2y) in it.
1) 2 (2x + y = 5)
1) 4x + 2y = 10
2) -5x - 2y = -6
Add equations together.
x=-4
Plug in (-4) for x in equation 1.
2x + y = 5
2(-4) + y = 5
-8 + y = 5
Add 8 to both sides of the equation.
y = 13
(-4, 13)
So no, (-4, 12) is not the correct answer.
~Hope I helped!~